Selective ganglioside desialylation in the plasma membrane of human neuroblastoma cells* - Kopitz, Jürgen; Reitzenstein, Carolina von; Sinz, Karin; Cantz, Michael (Glycobiology, 1996)
Gangliosides of the plasma membrane are important modulators of cellular functions. Previous work from our laboratory had suggested that a plasma membrane sialidase was involved in growth control and differentiation in cultured human neuroblastoma cells (SK-N-MC), but its substrates had remained obscure. We now performed sialidase specificity studies in subcellular fractions and found ganglioside GM3 desialylating activity in presence of Triton X-100 to be associated with the plasma membrane, but absent in lysosomes. This Triton-activated plasma membrane enzyme desialylated also gangliosides GDla, GD1b, and GT1b, thereby forming GM1; cleavage of GM1 and GM2, however, was not observed. Sialidase activity towards the glycoprotein fetuin with modified C-7 sialic acids and towards 4-methylumbelliferyl neuraminate was solely found in lysosomal, but not in plasma membrane fractions.The role of the plasma membrane sialidase in ganglioside desialylation of living cells was examined by following the fate of [3H]galactose-labelled individual gangliosides in pulse-chase experiments in absence and presence of the extracellular sialidase inhibitor 2-deoxy-2,3-dehydro-N-acetylneuraminic acid. When the plasma membrane sialidase was inhibited, radioactivity of all gangliosides chased at the same rate. In the absence of inhibitor, GM3, GD1a, GD1b, GD2, GD3 and GT1b were degraded at a considerably faster rate in confluent cultures, whereas the GM1-pool seemed to be filled by the desialylation of higher gangliosides. The results thus suggest that the plasma membrane sialidase causes selective ganglioside desialylation, and that such surface glycolipid modification triggers growth control and differentiation in human neuroblastoma cells.
Gesehen am 10.07.2024